Исследование кургана бронзового века в г. Николаев - Гребенников, Ю.С.; Горбенко, К.В.; Каравайко, Д.В.; Карнаух, Е.Г. (Археологічні дослідження в Україні, 2010)
Materials from excavations at the Bronze Age barrow in Mykolayiv where 10 graves of Yamna and Catacomb cultures were discovered are presented to the scientific circulation.